2009
DOI: 10.1128/aem.01350-08
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and Activity of Methanotrophic Bacteria in Littoral and Profundal Sediments of Lake Constance (Germany)

Abstract: The abundances and activities of aerobic methane-oxidizing bacteria (MOB) were compared in depth profiles of littoral and profundal sediments of Lake Constance, Germany. Abundances were determined by quantitative PCR (qPCR) targeting the pmoA gene and by fluorescence in situ hybridization (FISH), and data were compared to methane oxidation rates calculated from high-resolution concentration profiles. qPCR using type I MOB-specific pmoA primers indicated that type I MOB represented a major proportion in both se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
58
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 65 publications
13
58
0
Order By: Relevance
“…Hence, type I was most likely the dominant group of methanotrophic bacteria in all of these sediments. This finding is in agreement with other studies in sediments of freshwater habitats (Boschker et al 1998, Costello et al 2002, Eller et al 2005, Rahalkar et al 2009). Boschker et al (1998) showed the dominance of type I methanotrophs for the first time with C 13 -methane labeling experiments.…”
Section: Discussionsupporting
confidence: 83%
“…Hence, type I was most likely the dominant group of methanotrophic bacteria in all of these sediments. This finding is in agreement with other studies in sediments of freshwater habitats (Boschker et al 1998, Costello et al 2002, Eller et al 2005, Rahalkar et al 2009). Boschker et al (1998) showed the dominance of type I methanotrophs for the first time with C 13 -methane labeling experiments.…”
Section: Discussionsupporting
confidence: 83%
“…This presentation of a direct and statistically significant linear relationship is the first to our knowledge. It agrees with other qualitative reports of positive correlations between methane oxidation rates and abundance of pmoA or MOB 16S rRNA genes determined using a variety of methods -quantitative PCR, FISH, or sequencing -for marine water column and lake sediments (Crespo-Medina et al, 2014;Deutzmann et al, 2011;Rahalkar et al, 2009;Steinle et al, 2015). Future application of marine-specific pmoA primers may further improve this correlation (Tavormina et al, 2008).…”
Section: Abundances Of Mob and Non-mob Methylotrophs Control The Methsupporting
confidence: 77%
“…The finding that the maximum of methanotrophic activity in Lake Kinneret occurred where oxygen concentrations were below the detection limit is in agreement with recent results from littoral and profundal sites in Lake Constance (Rahalkar et al 2009). Similarly, in the Black Sea water column, aerobic methanotrophs and methane oxidation were recorded at water depths in which oxygen concentration was below the detection limit (Schubert et al 2006).…”
Section: Discussionsupporting
confidence: 81%
“…Similarly, in the Black Sea water column, aerobic methanotrophs and methane oxidation were recorded at water depths in which oxygen concentration was below the detection limit (Schubert et al 2006). It is still unclear whether methanotrophs are responsible for the methane oxidation under these conditions (Schubert et al 2006, Rahalkar et al 2009), since they require oxygen as an electron acceptor. It has been postulated that MOB can also be responsible for methane oxidation under anaerobic conditions (Rahalkar et al 2009), probably by using an alternative terminal electron acceptor like nitrate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation